HUBUNGAN ANTARA ADVERSITY QUOTIENT DENGAN KEMANDIRIAN DALAM PENGAMBILAN KEPUTUSAN KARIR PADA SISWA KELAS XI SMK NEGERI 2 SURABAYA - IRA PRATIWI (Universitas Negeri Surabaya, 2013)
Abstract : This study aims to determine the relationship between adversity quotient with the independence in career decision-making on XI grade student of SMK Negeri 2 Surabaya . The design in used of the study is correlational. The subjects in this study were XI grade students of SMKN 2 Surabaya, which amounts to 87 students. Analytical technique used was correlation analysis technique product moment from Pearson. The results of this study showed that adversity quotient has significant correlation with independence in career decision-making with positive direction of correlation which can be seen from the level of significance which of 0.000 (<0.05) and the correlation coefficient of 0.731. The conclusion of this study is that there is a positive relationship between adversity quotient with independence in career decision- making. Key words: adversity quotient, independence in career decision-making Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara adversity quotient dengan kemandirian dalam pengambilan keputusan karir pada siswa kelas XI SMK Negeri 2 Surabaya. Rancangan penelitian yang digunakan adalah korelasional. Subyek pada penelitian ini adalah siswa kelas XI SMKN 2 Surabaya yang berjumlah 87 siswa. Teknik analisis yang digunakan adalah teknik analisis korelasi product moment dari Pearson. Hasil penelitian ini menunjukkan bahwa adversity quotient memiliki hubungan yang signifikan dengan kemandirian dalam pengambilan keputusan karir dengan arah hubungan yang positif yang dapat dilihat dari nilai signifikan sebesar 0,000 (<0,05) dan koefisien korelasi 0,731. Kesimpulan dari penelitian ini adalah ada hubungan positif antara adversity quotient dengan kemandirian dalam pengambilan keputusan karir. Kata kunci : adversity quotient, kemandirian dalam pengambilan keputusan karir.